An empirical study of the complexity of requirements management in construction projects. Issue 5 (19th August 2014) - Jallow, Abdou Karim; Demian, Peter; Baldwin, Andrew N.; Anumba, Chimay
Abstract : Purpose: The aim of this paper was to investigate in-depth the current approach of managing client requirements in construction and to highlight the significant factors, which contribute to the complexity of managing the requirements in order to define a better approach. Design/methodology/approach: A case study of a leading international global built asset and engineering consultancy organization was conducted over two years. The case study was conducted principally using semi-participant observations supplemented with other qualitative data collection methods (i.e., interviews, questionnaires and document analysis). Thematic analysis was used to analyse the data. Findings: The results highlight major factors associated with the complexity of managing client requirements information, which include: mechanisms for documentation, storage and access, distribution of requirements information between stakeholders and across lifecycle phases of a project, traceability management and the provision of effective change management incorporating dependency checking and impact analysis. Research limitations/implications: The main limitation of the research is the use of an in-depth study of a single organization, which applied the same project management method across all the projects they managed. Further work is planned to develop the proposed framework fully, and develop a software platform to operationalize and evaluate its industrial applicability with construction projects. Practical implications: The implications of this research is that a better approach to managing requirements information is needed, which will facilitate the design, construction and operations of buildings within budget and time. An integrated framework and an associated tool are suggested to implement the approach. Originality/value: This study identifies major research gaps and problems in the AEC/FM industry; proposes and presents eRIM framework to facilitate lifecycle management of the requirements.